E-Commerce, Efikasi Diri Dan Infrastruktur Keuangan Sebagai Pendorong Keputusan Berwirausaha Mahasiswa Akuntansi - Aliah, Nur; Faridani, Mutia Riska; Muda, Iskandar; Abdullah, Noor Marini Haji (Universitas Hamzanwadi, 2025)
The purpose of this study was to determine whether e-commerce, self-efficacy and financial infrastructure can influence accounting students' decisions to become entrepreneurs. This study was motivated by the development of technology that has changed the mindset of accounting students to be more creative and innovative so that students' interest in becoming entrepreneurs has increased. The results of this study indicate the influence of e-commerce on accounting students' entrepreneurial decisions, self-efficacy influences accounting students' entrepreneurial decisions and financial infrastructure with accounting information systems influences accounting students' entrepreneurial decisions. Technological developments with the emergence of e-commerce provide great opportunities for students to start businesses with lower barriers. Students who have a high level of self-efficacy will be more confident in managing a business, taking risks and solving problems that arise in the entrepreneurial process. This is in accordance with behavioral theory which states that the perception of control over behavior greatly determines the emergence of intentions and ultimately entrepreneurial actions. Accounting students, who are basically equipped with the ability to understand financial recording and reporting systems, have a competitive advantage and can make business decisions appropriately.